Role of CD47 in Hematological Malignancies - Eladl, Entsar; Tremblay-LeMay, Rosemarie; Rastgoo, Nasrin; Musani, Rumina; Chen, Wenming; Liu, Aijun; Chang, Hong (Journal of hematology and oncology, 2020)
CD47, or integrin-associated protein, is a cell surface ligand expressed in low levels by nearly all cells of the body. It plays an integral role in various immune responses as well as autoimmunity, by sending a potent “don’t eat me” signal to prevent phagocytosis. A growing body of evidence demonstrates that CD47 is overexpressed in various hematological malignancies and its interaction with SIRPα on the phagocytic cells prevents phagocytosis of cancer cells. Additionally, it is expressed by different cell types in the tumor microenvironment and is required for establishing tumor metastasis. Overexpression of CD47 is thus often associated with poor clinical outcomes. CD47 has emerged as a potential therapeutic target and is being investigated in various preclinical studies as well as clinical trials to prove its safety and efficacy in treating hematological neoplasms. This review focuses on different therapeutic mechanisms to target CD47, either alone or in combination with other cell surface markers, and its pivotal role in impairing tumor growth and metastatic spread of various types of hematological malignancies.